Mission Titanic [compact disc, unabridged] - Watson, Jude (39 clues. Doublecross, 2015)
At only seventeen years old, Ian Kabra is head of the Cahills, the most powerful family in the world. He has presidents on speed dial, generals at his beck and call. Ian knows he's an ideal leader and the only man enough for the job. There's just one small problem: He's already messed up big-time.